DEVELOPMENT OF VIDEO-BASED MULTIMEDIA FOR JAVANESE LANGUAGE SUBJECTS MATERIAL MACA GEGURITAN THROUGH DICK AND CAREY MODEL - Novita Aprilianti; Ibut Priono Leksono; Ujang Rohman (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2023)
The objectives of this development are to (1) Produce video-based multimedia for Javanese subjects as learning support media, (2) Know the effectiveness of using video-based multimedia for Javanese subjects as learning support media, and (3) Know the attractiveness of using video-based multimedia for Javanese subjects as supporting media for class VII as supporting media Learning. The development model in this study uses the Dick Carey method. Material experts, design experts, and learning media experts are all involved in the development process to provide input and suggestions for improvement. In addition, colleagues who are Javanese language teachers at SMPN 23 Surabaya and students as users as well as targets for the development of video-based multimedia Javanese subjects maca geguritan material SMPN 23 Surabaya also provided comments and suggestions for development products so that they are good and suitable for use. The Use of Video-Based Multimedia Development for Javanese Language Subjects Maca Geguritan Material Through the Dick and Carey Model at SMPN 23 Surabaya can effectively increase active learning interaction. Video-Based Multimedia Products Javanese Language Subjects Maca Geguritan material is the final product of this development research project. The substance, learning design, and feasibility of learning media from these experts are all at a very decent level. The feasibility of small group trials and field trials with qualifications, meanwhile, is very high and does not require revision.